Long range magnetic ordering with giant magnetic moments in Pt doped NiMn thin films - (:unkn) unknown (AMER INST PHYSICS, 2009)
Magnetization and electron spin resonance (ESR) measurements have been carried out on a 1.2 at. % Pt doped NiMn thin film (100 angstrom) in the temperature range of 5-150 K for both parallel (magnetic field parallel to the film surface) and perpendicular configurations. M versus H loops were recorded for each configuration at 5, 40, and 120 K. We have observed a number of differences between M versus H loops: for the perpendicular configuration, the hysteresis loops shift as a whole along the negative field axis (22 Oe at 5 K and 15 Oe at 120 K) for the field cooling case as a manifestation of the rigid component of the unidirectional anisotropy field, while no shift was observed for the parallel configuration. In addition, for the perpendicular configuration, M goes to the technical saturation value at a field much less than the corresponding demagnetization field (similar to 4 pi M-s), indicating that this sample has a large bulk uniaxial anisotropy perpendicular to the film surface. It is also interesting that the observed saturation magnetization is much larger than the value (similar to 10.2 kOe) corresponding to the full alignments of Ni and Mn moments, exceeding the experimental uncertainty, leading us to suggest that orbital magnetism may be responsible for the enhanced saturation magnetization. Furthermore, the exchange stiffness constant (D), bulk anisotropy constant, and surface anisotropy constant were deduced from ESR data analysis. Based on magnetization and ESR results, we conclude that the magnetic behavior is compatible with the ESR fitting parameters. We also show that the competing asymmetric surface effects due to magnetostatic interactions play a crucial role in the overall magnetic behavior of this film. (C) 2009 American Institute of Physics. [DOI: 10.1063/1.3075858]
Keywords: THERMOMAGNETIC HYSTERESIS